Proceedings of the International Conference of Health Development. Covid-19 and the Role of Healthcare Workers in the Industria 2020
DOI: 10.2991/ahsr.k.201125.062
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Quality of Life in Patient With Chronic Kidney Disease Based on Frequency of Hemodialysis in the Community: A Research During Covid-19

Abstract: Background: The incidence of chronic kidney disease has been increased every year. One of the treatment in these cases is hemodialysis. Hemodialysis can affect physical dan psychological that affect quality of life in patients. This study was conducted to analyze the differences in quality of life based on frequency of hemodialysis on chronic kidney patients in community. Methods: This research uses a cross sectional design and done at 66 sample with the sampling method of purposive sampling. Data collection u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…[ 1 , 35 ] Data from Ethiopia suggested socioeconomic and educational status on top of higher hemoglobin levels were significant determinants for improved QoL. [ 2 ] Higher BMI and duration of dialysis onset >5 years were associated with poor QoL in an Iranian population; however, these variables are insignificant in our findings. [ 35 ] Previous studies from Pakistan have suggested presence of diabetes and duration of dialysis onset negatively correlating with QoL.…”
Section: Discussionmentioning
confidence: 70%
See 4 more Smart Citations
“…[ 1 , 35 ] Data from Ethiopia suggested socioeconomic and educational status on top of higher hemoglobin levels were significant determinants for improved QoL. [ 2 ] Higher BMI and duration of dialysis onset >5 years were associated with poor QoL in an Iranian population; however, these variables are insignificant in our findings. [ 35 ] Previous studies from Pakistan have suggested presence of diabetes and duration of dialysis onset negatively correlating with QoL.…”
Section: Discussionmentioning
confidence: 70%
“…[ 8 ] Twice-weekly sessions of dialysis were popular among older Caucasian women and individuals suffering from Human Immunodeficiency Virus (HIV) and Acquired Immunodeficiency Syndrome (AIDS) according to study mentioned above. [ 32 ] Majority of studies stated better QoL among individuals adjusting with twice-weekly sessions of dialysis as compared to thrice-weekly sessions, [ 2 , 7 , 30 , 33 ] while a study recorded no difference of QoL among both frequencies of dialysis. [ 8 , 31 ] Impaired mental status, disturbances of sleep, decline in sexual and cognitive function was prominent among patients with thrice-weekly schedule of dialysis.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations